An overview on the seismic behaviour of timber frame structures - Vasconcelos, Graça (2013)
Traditional timber frame walls are an important structural element of many buildings and are usually composed of vertical posts and horizontal beams with bracing diagonal elements. In Portugal the timber frame walls, known as frontal walls, are usually part of Pombalino buildings, which were introduced by the Marquis of Pombal, who was responsible for the reconstruction of Downtown Lisbon after the great earthquake of 1755, which partially destroyed the city. Given the increasing interest of the research community to this structural system, it is important to promote the discussion of the main findings that can contribute to the advance on the knowledge of the mechanical behaviour of timber frame buildings to seismic action. Therefore, this paper intends: (1) to give an overview of the different solution of timber frame structures in different countries with special focus on the frontal walls characteristic of Pombalino buildings; (2) provide some examples of the reasonable behaviour of timber frame buildings in past earthquakes; (3) to summarize the experimental research carried out in the recent years in analysis of the behaviour to in-plane cyclic loading.